EVALUATION OF WORK POSITION USING SUBYECTIVITY APPROACH BASED ON RULA METHOD - ahmad hanafi (Center for Study and Journal Management FTI UMI, 2021)
Workers' activities basically have a positive and negative impact, one of which is the result of a disturbed skeletal and muscular system, which is a decrease in the strength level of body parts which constitutes work productivity when carrying out daily activities. Knowing the danger level of body posture carried out by the welding position, so that it can be given useful input for the company's progress. The method used is the Rapid User Limb Assessment (RULA) method carried out on welding workers and the research method quantitatively and qualitatively then carried out statistical analysis, subjectivity and rula. The results showed that the final score of the posture of squatting, sitting and sitting in a chair had a score of 7, which means a high level of risk and needs immediate improvement. After evaluating the welding position improvement, there is a seat posture with a score of 3 which is a low risk level and requires changes. Same with the welding position sitting on the chair. The squat welding position with a score of 4 which is a low level risk level and sitting work posture has a score of 4 which means a low risk level, but requires a change for the future. From this study it was found that the relationship between Nordic Body Map and RULA was a continuity in squat work postures, which was found that this work posture had the highest risk of danger. Need to improve work posture in certain welding positions in this project or provide counseling about the dangers of work in the work posture if it continues